The problems of Alash studies in the journalism of Tursynbek Kakishev - Ashirbekova Г.; Akhmet К.; Begaidarova Ж.Е. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article analyzes and concludes about the study of the problem of Alash studies in the journalism of scientist T.Kakishev, the civil position and personal views of the author in it. The scientist’s writings are dominated by factuality, which considered the circumstances that influenced the development of the opposite view of the idea of Alash in the history and literature of the Soviet period, which has not yet been fully studied. Special attention is paid to research methods in journalistic articles in which the scientist cited statistical data concerning the fate of the slanderous national intelligentsia, which suffered from political ideologies that took place in different periods of national history. Conclusions about the fate of the Kazakh intelligentsia, published in the newspapers «Zhuldyz», «Leninshil Zhas», reveal the scientist in a new light. T.Kakishev pays special attention to the activities of the press when considering the history of literary criticism, a research essay about the journal «Sadak», published by students of the madrasa «Galiya» in Ufa, works from journalistic trips to regional studies, personal study, is a sample of collecting and generalizing, analyzing, forecasting information. The articles of the scientist «Kiyas kisyndar kiyameti», «Kagidaga ainalgan kateler tuzelse», «Ult ziyalylaryn tagdyr-talayy» explain the conclusions concerning the historical event and the political situation of that period, as well as the slanderous statements of the Alash intelligentsia. The article reveals the methods of analysis of works, printed articles on the topic of a scientist who comprehensively investigated the problem of Alash studies.